2021
DOI: 10.1155/2021/5563073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Components and Traditional Chinese Medicine on Hypertension: A Potential Role for Gut Microbiota

Abstract: Hypertension (HTN) is an important worldwide public health issue affecting human health. The pathogenesis of HTN involves complex factors such as genetics, external environment, diet, and the gut microbial dysbiosis. The gut microbiota, as a medium of diet and drug metabolism, is closely correlated to host’s health and disease (including HTN). Literatures were randomly collected from various databases including PubMed, ScienceDirect, Google Scholar, and China National Knowledge Infrastructure (CNKI). In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 110 publications
(141 reference statements)
0
7
0
Order By: Relevance
“…However, the Firmicutes population in neonatal gut was much greater in SHR than in neonatal WKY. A higher Firmicutes to Bacteroidetes ratio (F/B ratio) is considered to be a hallmark of hypertension (Yang et al, 2015;Zhang et al, 2021). Indeed, in our study, the neonatal SHR had much greater F/B ratio than neonatal WKY, primarily because early neonatal gut is devoid of Bacteroidota taxa.…”
Section: Discussionmentioning
confidence: 55%
“…However, the Firmicutes population in neonatal gut was much greater in SHR than in neonatal WKY. A higher Firmicutes to Bacteroidetes ratio (F/B ratio) is considered to be a hallmark of hypertension (Yang et al, 2015;Zhang et al, 2021). Indeed, in our study, the neonatal SHR had much greater F/B ratio than neonatal WKY, primarily because early neonatal gut is devoid of Bacteroidota taxa.…”
Section: Discussionmentioning
confidence: 55%
“…We need to learn how to use and not abuse this system. It is easy to mistreat the PVS system with an improper diet and populated environment [33]. Supplementary research is required to determine ways to control PVS; however, ancient knowledge of Eastern medicine gives important lessons in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TCM may be a promising treatment for CVDs. Recent studies have shown that TCM may improve the symptoms of hypertension by regulating gut microbiota [ 555 ]. Baicalin and berberine have been found to reduce left ventricular hypertrophy and change the intestinal microbiota to improve hypertension [ 481 ].…”
Section: Promising Therapy Of Targeting the Gut Microbiota In Cvdsmentioning
confidence: 99%